Pemanfaatan TOGA (Tanaman Obat Keluarga) Dalam Meningkatkan Kualitas Kesehatan Masyarakat Labuhan Bilik - Khairun Nisa; Nurliza Dora (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
Using land for the growing of medicinal plants that may be utilized for everyday needs is known as"living pharmacy." The Family Medicinal Plant (TOGA) is the common name for this Living Pharmacy among the neighborhood. Indonesia's tropical environment make farming there highly viable. Forthis reason, it's critical to utilize undeveloped land to establish a profitable pharmacy. Creating a living pharmacy aims to disseminate information on how to cultivate and utilize herbal plants for enhancing and preserving health. The preparation and implementation phases of creating a functioning pharmacy make up the demonstration approach that is employed.The benefits of operating a living pharmacy in the village inelude raising awareness of which plants are suitable for herbal remedies medication and cultivation methods. In order for the local community to use the herbs from the outcomes of producing living to create herba mixtures or herbs to promote health